Identification of a novel likely pathogenic TPM1 variant linked to hypertrophic cardiomyopathy in a family with sudden cardiac death - Amir Azimi; Mahdieh Soveizi; Alireza Salmanipour; Mohammadhossein Mozafarybazargany; Amir Ghaffari Jolfayi; Majid Maleki; Samira Kalayinia (ESC Heart Failure, 2024)
Abstract Aims Hypertrophic cardiomyopathy (HCM) is an autosomal dominant genetic cardiac disorder characterized by unexplained left ventricular hypertrophy. It can cause a wide spectrum of clinical manifestations, ranging from asymptomatic to heart failure and sudden cardiac death (SCD). Approximately half of HCM cases are caused by variants in sarcomeric proteins, including α‐tropomyosin (TPM1). In this study, we aimed to characterize the clinical and molecular phenotype of HCM in an Iranian pedigree with SCD. Methods and Results The proband and available family members underwent comprehensive clinical evaluations, including echocardiography, cardiac magnetic resonance (CMR) imaging and electrocardiography (ECG). Whole‐exome sequencing (WES) was performed in all available family members to identify the causal variant, which was validated, and segregation analysis was conducted via Sanger sequencing. WES identified a novel missense variant, c.761A>G:p.D254G (NM_001018005.2), in the TPM1 gene, in the proband, his father and one of his sisters. Bioinformatic analysis predicted it to be likely pathogenic. Clinical features in affected individuals were consistent with HCM. Conclusions The identification of a novel TPM1 variant in a family with HCM and SCD underscores the critical role of genetic screening in at‐risk families. Early detection of pathogenic variants can facilitate timely intervention and management, potentially reducing the risk of SCD in individuals with HCM.